Staphylococcus aureus in Polymicrobial Skinand Soft Tissue Infections: Impact of Inter-Species Interactionsin Disease Outcome - Florencia Mariani; Estela Maria Galvan (MDPI AG, 2023)
Polymicrobial biofilms provide a complex environment where co-infecting microorganisms can behave antagonistically, additively, or synergistically to alter the disease outcome compared to monomicrobial infections. Staphylococcus aureus skin and soft tissue infections (Sa-SSTIs) are frequently reported in healthcare and community settings, and they can also involve other bacterial and fungal microorganisms. This polymicrobial aetiology is usually found in chronic wounds, such as diabetic foot ulcers, pressure ulcers, and burn wounds, where the establishment of multi-species biofilms in chronic wounds has been extensively described. This review article explores the recent updates on the microorganisms commonly found together with S. aureus in SSTIs, such as Pseudomonas aeruginosa, Escherichia coli, Enterococcus spp., Acinetobacter baumannii, and Candida albicans, among others. The molecular mechanisms behind these polymicrobial interactions in the context of infected wounds and their impact on pathogenesis and antimicrobial susceptibility are also revised.